2021
DOI: 10.1016/j.heliyon.2021.e06150
|View full text |Cite
|
Sign up to set email alerts
|

Phytomelatonin in stress management in agriculture

Abstract: Melatonin was discovered as a pineal gland hormone in animals and is now more significantly known as a signaling molecule in plants' biotic and abiotic stressors. Melatonin has been traced back to prokaryotic organisms during evolution and its primary function of antioxidant scavenging free radicals in photosynthetic prokaryotic bacteria is a lesser explored and exciting area for further research globally. The authors at IIT Delhi are trying to establish its potential role in stress management in agriculture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…•− and H 2 O 2 rates in the berries, which resulted in lower repining and senescence during storage [42]; these results are in agreement with some other reports that found that melatonin application significantly lowers the H 2 O 2 rate in stored peach and cassava [43,44]. Moreover, Wang et al [15] observed a decrease in O 2…”
Section: Discussionsupporting
confidence: 89%
“…•− and H 2 O 2 rates in the berries, which resulted in lower repining and senescence during storage [42]; these results are in agreement with some other reports that found that melatonin application significantly lowers the H 2 O 2 rate in stored peach and cassava [43,44]. Moreover, Wang et al [15] observed a decrease in O 2…”
Section: Discussionsupporting
confidence: 89%
“…As many plants are whole genome sequenced, and researchers have benefited from the availability of high-quality genomic data to find homologs of these enzymes. SNAT homolog was also reported in other species, including alga laver, cyanobacteria, apple, Arabidopsis, grapevine ( Tripathi et al, 2021 ). Furthermore, genome-wide studies have revealed that presence of these enzymes is diversified, with varied in frequency of existence in different plants.…”
Section: Transcriptomicsmentioning
confidence: 79%
“…Furthermore, ectopic overexpression of MzSNAT5 in Arabidopsis reported increased melatonin concentration and improve drought tolerance. Moreover, when the SNAT production in rice was suppressed, the adverse effects were observed on plant growth, and low melatonin levels ( Tripathi et al, 2021 ). It was certain that low melatonin levels have penalty of increased susceptibility to abiotic stresses and ultimately low yield levels.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…This role as a protective agent has been widely studied in many plant species and in multiple stressful situations. Several recent reviews on this topic can be consulted (Moustafa-Farag et al 2020a, c;Pardo-Hernández et al 2020;Sharma et al 2020;Nawaz et al 2020;Ahn et al 2021;Hernández-Ruiz 2021a, 2022;Hoque et al 2021;Tripathi et al 2021;Zhao et al 2021aZhao et al , 2022Giraldo-Acosta et al 2022). Generally, phytomelatonin actions through phytomelatonin receptor (PMTR1), and it appears to activate metabolic, hormonal, and defense responses, providing the plant with greater tolerance against biotic/abiotic stressor (Wei et al 2018a;Wang et al 2021;Yang et al 2021;Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%